Audel HVAC fundamentals. - Brumbaugh, James E. (Audel Technical Trades Series., 2004)
Your guide to keeping the heat onWhether you're an apprentice or a veteran HVAC technician, you know that technology changes and you need to keep up. This fully revised guidebook covers everything you need to know to install, maintain, and repair the components that run, regulate, and fuel both old and new systems. From oil burners and steam line controls to the newest chip-based technology and environmental regulations, Volume 2 helps you keep the heat on.* Install and repair thermostats, humidistats, automatic controls, and oil or gas burner controls* Review pipes, pipe fitti.